TURNOVER ANALYSIS OF NURSES IN SANTA FAMILIA HOSPITAL - Nurhasanah, Nurhasanah; Hurang, Christianus Natalis; Andrea, Reza (STMIK Widya Cipta Dharma, 2023)
Job satisfaction was an emotional state in which an employee felt that tasks or work, superiors, work situation, and organization were enjoyable. Job satisfaction had a contribution to reducing turnover rates and increasing employee commitment. The purpose of this service was to problem identification, analyze problems, find solutions, and provide recommendations to Santa Familia Hospital. The results of this community service were a job satisfaction survey for nurses, which indicated that 36% were dissatisfied, 53% were low satisfied, and 11% were satisfied. A fishbone analysis revealed several causes of nurse turnover, namely from the factors of man, money, material, and method. A plan of activities as a solution to the problem was created with a total of 11 activities. Recommendations were formulated, totaling 7, for Santa Familia Hospital to address the identified problems. The conclusion of this community service was that the job satisfaction of nurses at Santa Familia Hospital was low, which could lead to turnover intentions among employees, ultimately resulting in turnover.